Measuring Metrics of Climate Change and Its Implication on the Endangered Mammal Conservation in the Leuser Ecosystem - Condro, Aryo Adhi; Prasetyo, Lilik Budi; Rushayati, Siti Badriyah; Santikayasa, I Putu; Iskandar, Entang (Frontiers in Environmental Science, 2021)
The Leuser Ecosystem is one of the essential landscapes in the world for biodiversity conservation and ecosystem services. However, the Leuser Ecosystem has suffered many threats from anthropogenic activities and changing climate. Climate shifting is the greatest challenge to global biodiversity conservation. Efforts should be made to elaborate climatic change metrics towards biological conservation practices. Herein we present several climate change metrics to support conservation management towards mammal species in the Leuser Ecosystem. We used a 30-year climate of mean annual temperature, annual precipitation, and BIOCLIM data to capture the current climatic condition. For the future climate (2050), we retrieved three downscaled General Circulation Models for the business-as-usual scenario of shared socio-economic pathways (SSP585). We calculated dissimilarities of the current and 2050 climatic conditions using the standardized Euclidean distance (SED). To capture the probability of climate extremes in each period, we calculated the 5th and 95th percentiles of the distributions of monthly temperature and precipitation, respectively, in the current and future conditions. Furthermore, we calculated forward and backward climate velocities based on the mean annual temperature. These metrics can be useful inferences about species conservation. Our results indicate that almost all of the endangered mammals in the Leuser Ecosystem will occur in the area with threats to local populations and sites. Different conservation strategies should be performed in the areas likely to present different threats towards mammal species. Habitat restoration and long-term population monitoring are needed to support conservation in this mega biodiversity region.